ФОРМУВАННЯ СЛУЖБИ КОНТРОЛІНГУ РИЗИКІВ В КОМЕРЦІЙНИХ БАНКАХ УКРАЇНИ (International Journal of Innovative Technologies in Economy, 2018)
The author gave us some examples of formation of banking risks controlling and their need in Ukrainian commercial banks which, at the present stage of development, are in dare need of innovations both in sphere of management and in sphere of separate products development. The realization of controlling acquires special relevance, whereas the last is not just a management system which has absorbed the functions of accounting, planning, marketing and budget contol but also high-quality new sample of manager thinking addressed in future.Bank controlling is a functional system of planning, controlling and analyzing rejections, coordination, internal consulting and general information management of the bank. The main aim of controlling is orientation of management process for achievement of the goals of the bank. Nowadays, the market of providing controlling services in Ukraine is undeveloped, so that, it is expedient, creating of controlling companies or expansion of assortment of services of audit companies. In order to reduce the negative consequences of irrational management decisions the most effective are modern trends of services use of controlling company, whose specialists provide to bank the fulfillment of ultimate goals